The Feedback Given by University Supervisors to Student Teachers During Their Co-assessment Meetings - Maes, Olivier; Van Nieuwenhoven, Catherine; Colognesi, Stéphane (Frontiers in Education, 2022)
lThis qualitative study examines the levels of feedback given by university supervisors to student teachers during their co-assessment meeting in French-speaking Belgium. The co-assessment meeting is the final step in the internship supervision process and allows the student teacher to compare their self-evaluation with the cooperating teacher’s evaluation report and the supervisors’ evaluation. For this purpose, 14 co-assessment meetings were qualitatively analyzed. This analysis showed that the certification objective of the internship meeting influenced the level of feedback. Within this objective, the feedback was task-oriented. In the formative part of the meeting, the feedback was more process-oriented and self-regulatory. In this type of meeting, supervisors therefore adopt a dual perspective for feedback, both cognitivist and socio-constructivist. This perspective is part of a continuum logic